Effect of body-part specificity and meaning in gesture imitation in left hemisphere stroke patients. (22nd January 2021) - Tessari, Alessia; Mengotti, Paola; Faccioli, Luca; Tuozzi, Giovanni; Boscarato, Silvia; Taricco, Mariangela; Rumiati, Raffaella I.
Abstract: Previous studies showed that imitation of finger and hand/arm gestures could be differentially impaired after brain damage. However, so far, the interaction between gesture meaning and body part in imitation deficits has not been fully assessed. In the present study, we aimed at filling this gap by testing 36 unilateral left brain-damaged patients with and without apraxia (20 apraxics), and 29 healthy controls on an imitation task of either finger or hand/arm meaningful (MF) gestures and meaningless (ML) movements, using a large sample of stimuli and controlling for the composition of the experimental list. Left-brain damaged patients imitated ML finger worse than hand/arm movements, whereas they did not show the same difference in MF gesture imitation. In addition, apraxic patients imitated finger movements worse than hand/arm movements. Furthermore, apraxic patients' imitation performance was equally affected irrespective of the action meaning, whereas non-apraxic patients showed better imitation performance on MF gestures. Results suggest that MF gestures are processed as a whole, as imitation of these gestures relies on the stored motor programs in long-term memory, independently of the body part involved. In contrast, ML movements seem to be processed through direct visuo-motor transformations, with left-brain damage specifically disrupting imitation performance of the more cognitive demanding finger movements. Highlights: The meaning of gestures affects imitation in stroke patients. Finger gestures are sensitive to detect apraxic imitation deficits. Evidence for a dual-route model of gesture imitation is derived from observations of left-hemisphere stroke patients. Imitation of intransitive meaningful gestures is not influenced by body-parts. Imitation of meaningless movements is influenced by body-parts.